The F. L. Wright phenomenon and the “revolution in architecture” - Goryunov, Vasily (project baikal, 2022)
One of the most important aspects of Frank Lloyd Wright’s oeuvre did not receive sufficient analysis and evaluation. This concerns his place in the historical and architectural process of the late 19th – first half of the 20th century. This place is unique and incomparable with the importance of any other major architects of that time. The concept of “organic architecture” was the direct continuation and development of the ideas of the Art Nouveau period, although it also had a definite imprint of the avant-garde ideology. Frank Lloyd Wright’s path is an evolutionary path, and the height of his popularity coincides with the period of departure of Modern Architecture from the radicalism of its initial stage and with the restoration of the rights of architecture as a full-fledged branch of art. The oeuvre of Frank Lloyd Wright demonstrates the return of Modern Architecture to the principles of the Art Nouveau period in general and, in particular, to the romantic tradition.